The influence of upper limb immobilization on lower limb muscular activity during the sit-to-stand task - Leal, Viviana (2019)
The aim of this study was to compare the magnitude and pattern of lower limb muscular activity during the sit-to-stand (STS) task with and without upper limb immobilization. The activity of six muscles from each lower limb (Rectus Femoris, Vastus Medialis, Biceps Femoris, Tibialis Anterior, Gastrocnemius Medialis and Soleus) were recorded while 19 young healthy participants performed the STS task with and without an arm sling on their dominant side. Myoelectric signals were collected using BioPlux Research device, and two Bertec force platforms were used to determine different phases of the STS task. The peak of muscular activity and muscle onset times were calculated, two general linear models with an alpha of 0.05 were used between the conditions with and without upper limb immobilization. We found no statistically significant differences in the onset of lower limb muscular activity, and we observed decreased peak of muscular activity in the Rectus Femoris at the immobilized side and an increased peak in the Vastus Medialis at the side opposite to the upper limb immobilized compared to the control condition. We did observe differences in the magnitude of ipsilateral Rectus Femoris and contralateral Vastus Medialis as a consequence of upper limb immobilization.